Cerebral hypoperfusion due to rapid blood pressure control in a patient with type B aortic dissection: A case report - Yikun Zhao; Heng Li; Yuanyuan Guo (SAGE Open Medical Case Reports)
Type B aortic dissection represents a life-threatening cardiovascular event, necessitating a comprehensive treatment approach that includes anti-impulse therapy for blood pressure and heart rate control, movement restriction, analgesia, sedation, and consideration of subsequent endovascular or open surgery. Management of acute aortic dissection involves stringent blood pressure control to prevent extension of the dissection, which is critical in both surgical preparation and conservative treatment strategies. While the treatment regimen is relatively well-established, and early and long-term follow-up results are promising, there have been reports of adverse events during treatment. In this context, we present a case of a 40-year-old male with acute type B aortic dissection who developed cerebral hypoperfusion as a consequence of rapid blood pressure reduction, underscoring the need for balanced hemodynamic management. Following thoracic endovascular aortic repair surgery and hyperbaric oxygen therapy, the patient fully recovered 6 months later with no lingering sequelae. While current guidelines emphasize specific numerical values for blood pressure control in type B aortic dissection, the case underscores the potential need for a more individualized approach tailored to the unique characteristics of each patient.